Shielding a high‐sensitivity digital detector from electromagnetic interference. (15th June 2018) - Hintenlang, David E.; Jiang, Xia; Little, Kevin J.
Abstract: Purpose: To document a study in shielding a high‐sensitivity digital mammography system detector from AC magnetic fields of magnitudes great enough to induce imaging artifacts. Methods/materials: Preliminary evaluation of AC magnetic fields at a site designated for a digital breast tomosynthesis (DBT) system raised concerns that the magnetic component of electromagnetic interference (EMI) may be great enough to induce imaging artifacts. Subsequent measurements using digital detector arrays from two separate manufacturers verified this concern, and AC magnetic fields were mapped, spatially and temporally, throughout the area of concern. A simple shielding model was developed to elucidate the physics of extremely low‐frequency (ELF) EMI shielding and independently verify a commercial group's proposed shielding design and installation. Postshielding measurements were performed to demonstrate that the EMI fields were reduced to acceptable levels. Results: Preshielding measurements showed AC magnetic fields significantly exceeding manufacturers' tolerances for artifact‐free imaging in DBT. Continuous measurements demonstrated that the EMI fields varied significantly over time. Some locations in the room routinely averaged above 30 mG and occasionally exceeded 100 mG. The source was attributed to an adjacent electrical supply room, and temporal changes of the EMI were attributed to variations of the building electrical loads. The proposed shielding primarily consisted of continuous aluminum (6.35 mm thickness) and was installed by a group specializing in electromagnetic field shielding. Postshielding measurements demonstrated that the EMI fields were significantly reduced, generally to less than 0.5 mG, and that the shielding effectively dampened the large variations due to dynamic building electrical loads. Subsequent installation and evaluation of a DBT system revealed no issues with imaging artifacts. Conclusions: The successful shielding of ELF EMI involves physical principles that are not commonly encountered by medical physicists. Modern high‐sensitivity digital detectors may be successfully shielded against imaging artifacts with careful application of these principles.